Recovery from Myalgic Encephalomyelitis/Chronic Fatigue syndrome developed after severe acute respiratory syndrome coronavirus 2 vaccination: A case report - Isaku Kurotori; Wataru Sasao; Masahiko Abe (PCN Reports)
Abstract Background Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a neurological adverse effect after severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccinations. However, clinicians do not recognize the condition well, and no case report has shown a full recovery. Case Presentation We present a 65‐year‐old Japanese female who experienced severe fatigue, postexertional malaise, orthostatic intolerance, and various symptoms after her third SARS‐CoV‐2 vaccination. Following thorough examinations and excluding other potential diagnoses, she met the diagnostic criteria for myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). The symptoms persisted for 30 months and improved ultimately with comprehensive treatment and a self‐management strategy, including pacing management, pharmacological treatments, and psychiatric interventions to support those struggling with the despair over the devastating symptoms. Conclusion This case report describes ME/CFS following the SARS‐CoV‐2 vaccination and its full recovery. It illustrates the importance of considering the differential diagnosis of psychiatric disorders and addressing the condition through psychiatric interventions. Our findings provide new insights into treating ME/CFS and the vaccination‐related adverse effects.